Metacognitive strategies and reading comprehension in university students - Alcas Zapata, Noel (2019)
The objective of this research study was to determine the influence of metacognition on the reading comprehension of students of a university in Lima (Peru). Methodologically, the hypothetical deductive method was used, with a quantitative approach and quasi-experimental design. The sample consisted of 62 students belonging to the specialty of education. The descriptive and inferential results demonstrated the influence of metacognition on the reading comprehension of the participating subjects. In all cases, the expected outcome was achieved, evidencing the effectiveness of the intervention carried out.